Real time water quality measurements and predictions for the Marina Catchments - Chen, Min. (2009)
Water quality measurement is available in various methods; however, most of these methods are carried out in the laboratories. In this project, the main focus is on real time water quality measurement, which means the water quality measurement is continuous, unlike those laboratory analyses. Real time water quality measurement is important for decisions-making regarding drinking water, water treatment and other recreational activities as well as public safety. Real time water quality measurement is made by using multi-parameter sensors, YSIs. These sensors are able to measure turbidity, conductivity, pH, temperature and dissolved oxygen on site, however, parameters such as total suspended solids (TSS), total nitrogen (TN), and total phosphorus (TP) are not measured, as they can only be measured in the laboratory. The aim of the project is to derive a relationship between the real time measurements and the laboratory measurements, mainly the relationship between turbidity and TSS. Studies were carried out mainly from August 2008 to March 2009 at Alexandra Canal, MC14. A correlation is derived based on a storm event on 26 September 2008 at MC14. The relationship between TSS (mg/L) and turbidity is linear, y = 0.8731x + 10.522 with regression coefficient R2 equals to 0.7688, where y is predicted TSS value and x is the Turbidity measured by YSI sensors. This correlation is later used to predict the TSS values and the monthly TSS loading for other storm events.